‘Accipiant Qui Vocati Sunt’: Richard Fleming's Reform Sermon at the Council of Constance - Nighman, Chris L. (The journal of ecclesiastical history, 2000)
On Passion Sunday in 1417 (28 March) a sermon known by its scriptural theme as ‘Accipiant qui vocati sunt’ was delivered at the general council of the Church then assembled in the south German city of Constance. Three centuries later it was edited by Hermann von der Hardt who characterised ‘Accipiant’ as ‘by far the most severe sermon in which the enormous crimes of prelates – especially love of money, ambition, luxury and ignorance – are revealed with the greatest liberty and are vehemently reproached, so that it is a wonder that the council heard it patiently’. In an earlier publication containing excerpts from this sermon, Hardt had described it in similar terms as being ‘not unlike a burning furnace in terms of its fiery passion and its vehement attack on the vices of the clergy’. More recently Heinrich Finke clearly agreed with these appraisals in describing ‘Accipiant’ as a ‘scharfe Reformpredigt’, for he did not bestow such adjectival emphasis on any other reform sermon listed in his register of the Constance sermons. Paul Arendt, a student of Finke's and the author of the only monograph devoted to the many surviving sermons from Constance, repeatedly commented on the severity of ‘Accipiant’, especially in his long chapter on ‘das Hauptthema unserer Prediger: Behandlung der Frage der kirchlichen Reform’.Hardt ascribed this sermon to Vitale Valentine OFM, bishop of Toulon. However, as the following analysis will show, it is certain that this ascription was based on conjecture and that another preacher actually delivered the sermon. Hardt's only source for his edition of ‘Accipiant’ was an Erfurt manuscript which is now in the Schlossbibliothek at Pommersfelden. Because this lacks a rubric or colophon identifying the author of the sermon, Hardt's attribution must have been inferred from internal evidence. Thus began the long tradition of Vitale Valentine's authorship of ‘Accipiant’ which has previously been accepted without question by scholars of these conciliar sermons.